2022
DOI: 10.1590/fst.31321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different treatments on chemical composition, physical, anti-nutritional, antioxidant characteristics and in vitro starch digestibility of green-kernel black bean flours

Abstract: Green-kernel black bean (Vigna cylindrica (L.) Skeels) were processed with various treatments including soaking, roasting, cooking, autoclave and germination. The effects of these treatments on the chemical compostion, mineral, anti-nutrients, antioxidant and physical properties of the resultant flours were analyzed. The results indicate that green-kernel black bean was excellent sources of dietary fiber (165.4 g/kg), magnesium (2190 mg/kg), anthocyanin (791.6 mg/kg) and phenolic compounds (4.4 g gallic acid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The autoclaving-time treatment reduces antioxidant activities in instant cassava leaves porridge with increasing time (Table 4). This finding agrees with (Le et al, 2022), who found that autoclave treatment reduced antioxidant capabilities in green-kernel black bean flours in terms of DPPH free radical scavenging capacity and ferric reducing antioxidant power (FRAP).…”
Section: Antioxidant Propertiessupporting
confidence: 92%
“…The autoclaving-time treatment reduces antioxidant activities in instant cassava leaves porridge with increasing time (Table 4). This finding agrees with (Le et al, 2022), who found that autoclave treatment reduced antioxidant capabilities in green-kernel black bean flours in terms of DPPH free radical scavenging capacity and ferric reducing antioxidant power (FRAP).…”
Section: Antioxidant Propertiessupporting
confidence: 92%
“…Among all cereal bulgur, autoclaved bulgur samples exhibit significantly lower protein content compared to those cooked using the boiling method (Table 2). This could be attributed to the sterilization process, as the autoclave provided a high level of heat treatment, which led to the denaturation, solubility, and partial degradation of protein (LE et al, 2022). Protein molecules maintain their structure through a combination of covalent and non-covalent bonds.…”
Section: Proximate Chemical Composition Of Bulgurmentioning
confidence: 99%
“…This decrease can be attributed to leaching, where water-soluble minerals are lost during the cooking process (Khan et al, 2013). The combined effect of water and high temperatures in both cooking methods likely leads to a partial loss of these soluble salts (LE et al, 2022). Analysis of bulgur samples revealed that triticale and oat bulgur had the highest ash content compared to the other tested cereal bulgur samples.…”
Section: Proximate Chemical Composition Of Bulgurmentioning
confidence: 99%
“…The DPPH radical scavenging ability assay is widely used to estimate the radical scavenging activity of natural compounds due to its rapidity and sensitivity (Le et al, 2022;Wang et al, 2018). The method is based on the reduction of the original purplered DPPH radical to yellow (non-radical form, DPPH-H) by providing hydrogen and electrons, with the maximum absorption value of the original purple-red colour at 517 nm being reduced (Shen et al, 2018).…”
Section: Superfine-grinding Enhances the In Vitro Antioxidant Activit...mentioning
confidence: 99%